2019
DOI: 10.1590/1980-5373-mr-2018-0872
|View full text |Cite
|
Sign up to set email alerts
|

Desilication of ZSM-5 and ZSM-12 Zeolites with Different Crystal Sizes: Effect on Acidity and Mesoporous Initiation

Abstract: In the present work, the desilication of the H-ZSM-5 and H-ZSM-12 zeolites with Si/AL ratios of 28 and 56 and crystal sizes of around 200 and 600 nm, respectively, was performed. Through electron transmission microscopy analysis, it was possible to verify the influence of aluminium gradients on smaller crystals in addition to the exact moment at which the formation of mesoporous is initiated inside the zeolitic framework. Moreover, the crystal size exerts a significant influence on the total amount of acid sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This shows that the electrostatic repulsion of Mg 2+ by the membrane was much higher than that of Na + , hence why the high rejection of MgCl 2 was observed. It can be concluded that the composite membranes in this study possess negatively charge surfaces due to the AlO 4 tetrahedra interactions with the SiOH of ZSM-22 nanoadditives [ 84 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the electrostatic repulsion of Mg 2+ by the membrane was much higher than that of Na + , hence why the high rejection of MgCl 2 was observed. It can be concluded that the composite membranes in this study possess negatively charge surfaces due to the AlO 4 tetrahedra interactions with the SiOH of ZSM-22 nanoadditives [ 84 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the desilication process, the uncontrolled degradation of the zeolite structure does not occur and other mesoporous parts with a wide pore size distribution formed in the sample. Furthermore, this justifies the occurrence of the characteristic isotherms of microporous materials in both the parent and alkali-treated samples (Ahmadpour and Taghizadeh 2015b;Gorzin et al 2019a;Sabino da Silva et al 2019;Pérez-Ramírez et al 2009).…”
Section: Textural Properties and Morphologymentioning
confidence: 70%
“…Similarly, in the desilication method, along with 1.0 g of parent material, 30 ml of (0.1 mol/L) sodium hydroxide solution was added in a round bottom flask and refluxed at 323 ℃ for 1 hour [60]. The base treated sample was collected after the treatment and centrifuged to wash with deionised water repeatedly till neutral pH in the filtrate was observed.…”
Section: Base Treatment (Desilication Method)mentioning
confidence: 99%